2007
DOI: 10.1017/s1755691007078401
|View full text |Cite
|
Sign up to set email alerts
|

Shell matrices of Recent rhynchonelliform brachiopods: microstructures and glycosylation studies

Abstract: Like most metazoan biomineralisations, the brachiopod shell is the end product of a biologically controlled calcification process. The main agent of the control is the extracellular matrix, which is secreted by the outer mantle epithelium. This matrix mediates the calcification process by allowing crystal nucleation and elongation in specific orientations and finally, by stopping crystal growth. The proteinaceous moiety of brachiopod shell matrices has been extensively studied. Less known are the post-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…collagen in bone, Currey, 2006). According to Gaspard et al (2008) relatively high amounts of glucosamine may suggest the presence of chitin in the shell matrix of the investigated rhynchonelliform brachiopods, while the group found several different proteins of 20-25 kDa, 37 kDa, and 50 kDa in different species as well as low molecular weight glycoproteins. Cusack et al (2000) had reported a 62 kDa glycosylated protein.…”
Section: Molecular Level 461 the Role Of Intra-crystalline Organicsmentioning
confidence: 95%
See 1 more Smart Citation
“…collagen in bone, Currey, 2006). According to Gaspard et al (2008) relatively high amounts of glucosamine may suggest the presence of chitin in the shell matrix of the investigated rhynchonelliform brachiopods, while the group found several different proteins of 20-25 kDa, 37 kDa, and 50 kDa in different species as well as low molecular weight glycoproteins. Cusack et al (2000) had reported a 62 kDa glycosylated protein.…”
Section: Molecular Level 461 the Role Of Intra-crystalline Organicsmentioning
confidence: 95%
“…Pokroy et al (2006) have shown for many carbonates of biologic origin, that heating of the material to 200 C results in a relaxation of the lattice parameters of the carbonate mineral, such that it is likely that the intra-crystalline organics strain the lattice, and the strain is released upon the decomposition of the biomolecules on heating. A recent accurate study of Gaspard et al (2008) has shed some light on the molecular constitution of the organic material in the shell, but the substance remains enigmatic owing to its complexity. Three major types of macromolecules are typically considered as relevant in biominerals: (i) phospholipids, which are the fundamental molecules composing biological cell membranes and vesicle membranes, (ii) polysaccharides, where chitin is the most abundant form used as a structural material by animals (AlSawalmih et al, 2008, Fabritius et al, 2009, and (iii) proteins, which are ubiquitous in all tissues, controlling functions (e.g.…”
Section: Molecular Level 461 the Role Of Intra-crystalline Organicsmentioning
confidence: 99%
“…Shells of bivalves and brachiopods are believed to mineralize primarily by biologically controlled extracellular processes (e.g., Crenshaw, 1980;Falini et al, 1996;Gotliv et al, 2003;Gaspard et al, 2007). The main control is a macromolecular matrix outside the cell in an area that will become the site of mineralization.…”
Section: Biomineralizationmentioning
confidence: 99%
“…All extracellularly formed biological hard tissues contain occluded biopolymers [50][51][52][53], these being developed as organic membranes, fibers or networks. The steadily advancing degradation of the organic component effects that the biologic aragonite becomes progressively more porous, thus channels are formed, through which the solution can reach inner sample regions.…”
Section: The Conversion Of Biologic Aragonitesmentioning
confidence: 99%